Analisis Praktik Klinik Keperawatan pada pasien diabetes melitus tipe 2 dengan intervensi pemberian edukasi self care terhadap kualitas hidup pasien diabetes melitus di Rumah Sakit Umum Daerah Prof. Dr. H. Aloei Saboe Kota Gorontalo - Rosalinda Pakaya; Nikmawati puluhulawa (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Diabet Mellitus is a sillent killer disease characterized by increased blood glucose levels and failure of insulin secretion or inadequate use of insulin in metabolism, so to maintain stable blood glucose requires insulin therapy or insulin secretion booster drugs( Oral Hypoglycemia Agent/ OHA). Objective: Able to provide and apply Clinical Practice Analysis of Nursing in Type 2 Diabet Mellitus Patients with Intervention to Provide Self- Care Education on the Quality of Life of Diabet Mellitus Patients. Method: The research design uses a descriptive analysis method form of a case study approach. The number of respondents in this study was 6 respondents World Health Organization experienced Type 2 Diabet Mellitus, informasi collection techniques namely interviews, observation, physical examination, documentation. Results: From the results of the study, nursing problems were obtained, namely the instability of blood glucose levels, The implementation carried out by the researcher was the provision of self- care education so that patients are more concerned about lifestyle to reduce the complications that will be caused, this study uses leaflets and SAP. Conclusion: After conducting research, it can be concluded that the six respondents did not maintain a healthy lifestyle and consume foods that contain lots of salt, and the six respondents rarely exercise